Society’s Support for Polish Soldiers during the Polish-Bolshevic War in the Light of the Local Press and Selected Archive Materials from The State Archive in Łódź - Kaniewska, Anna (Social consequences of war, 2024)
Organizing help for soldiers fighting on the war front was one of the most important initiatives on the part of society, in particular groups and circles not directly involved and not taking part in military operations. The subject of this paper is to present and explain selected aspects of this activity undertaken in Łódź during the war between Poland and Bolshevik Russia. Active organizations making efforts to organize multi-directional and multi-faceted assistance for Polish soldiers include: the Polish Soldier Aid Society, the Polish White Cross, the Polish Red Cross Society, the Local Branch in Łódź, and the Craft Resource in Łódź. Equally dynamic activities were carried out by smaller organizations, groups and associations, such as: the National Organization of Women and the Academic Women’s Club. The press was a valuable source material in this respect, from which references and notices appearing regularly in published messages were taken. The press titles used included: „Echo Łódzkie”, „Kurier Łódzki”, „Rozwój”, „Straż Polska”. The source database was supplemented with information from archival materials stored in the State Archives in Łódź, in particular in leaflets and correspondence received by the city authorities and charitable institutions.